HIPERREALITAS DALAM SOCIAL MEDIA (STUDI KASUS: MAKAN CANTIK DI SENOPATI PADA MASYARAKAT PERKOTAAN) - Fitria, Herlinda (Universitas Negeri Yogyakarta, 2015)
This study reviews the phenomenon of eating in restaurants that recently came out as a new lifestyle known as